Potret Konflik Batin dan Trauma dalam Novel Sendalu Karya Chavchay Syaifullah - Suryani, Intan; Hayati, Yenni (Lembaga Yasin AlSys, 2026)
This study was motivated by the importance of literary psychology studies in understanding the internal conflict and trauma of characters in modern Indonesian literary works. The novel Sendalu by Chavchay Syaifullah was selected because it presents the main character, Lumang, who experiences psychological pressure due to traumatic experiences since childhood. This study aimed to describe the forms of internal conflict, the forms of trauma, and the relationship between trauma and the internal conflict of the character Lumang in the novel Sendalu. This study used a qualitative approach with a descriptive method. The research data consisted of words, phrases, clauses, sentences, narratives, dialogues, and character actions related to internal conflict and trauma, while the data source was the novel Sendalu by Chavchay Syaifullah, published by Penerbit Buku Kompas in 2006. Data were collected through reading and note-taking techniques, then analyzed through the stages of identification, classification, interpretation, and conclusion drawing. The results showed that the internal conflict of the character Lumang appeared in four forms, namely obsession with 8 instances, depression with 5 instances, anxiety with 2 instances, and guilt with 3 instances. In addition, three forms of trauma were found, namely repressive trauma with 5 instances, repetitive trauma with 4 instances, and symbolic trauma with 1 instance. This study also found 9 instances indicating the relationship between trauma and internal conflict. These findings indicate that unresolved childhood trauma affects the character’s way of thinking, emotions, and behavior, thereby forming complex internal conflict. Thus, this study contributes to strengthening literary psychology studies, particularly regarding the relationship between traumatic experiences and internal conflict in modern Indonesian literary works.